DEVELOPING PRE-PERFORMANCE ROUTINES FOR ACROBATIC GYMNASTICS: A CASE STUDY WITH A YOUTH TUMBLING GYMNAST - Fernanda Faggiani; Allistair P. McRobert; Zoe Knowles (Science of Gymnastics Journal)
A mixed-method approach was used to examine the development and acquisition of a personalized pre-performance routine (PPR) by a male youth gymnast. The athlete completed the Test of Performance Strategies and participated in semi-structured interviews alongside video clips to examine PPR experience at pre and post intervention then at 6 months follow up. There was a perceived increase in the effective use of psychological skills post intervention. Moreover, the gymnast reported a consistent PPR prior to performance, demonstrating control and automaticity of his routine. The strategy used to develop the individual PPR and its potential use with young athletes more generally is discussed.